Progressive metastatic pheochromocytoma induced by multiple endocrine neoplasia type 2A with a lethal outcome. Issue 6 (6th September 2022) - Nishimoto, Koshiro; Santo, Noriaki Lukas; Yonamine, Masato; Takekoshi, Kazuhiro; Kaneko, Go; Shirotake, Suguru; Fukushima, Hisayo; Okada, Yoshitaka; Yasuda, Masanori; Sakurai, Akihiro; Oyama, Masafumi; Kanao, Kento
Abstract : Introduction: Patients with multiple endocrine neoplasia type 2A (MEN2A) harboring a pathological variant in the RET gene are characterized by medullary thyroid carcinoma (MTC), pheochromocytoma, and hyperparathyroidism. Although pheochromocytoma is currently defined as a malignant tumor, MEN2A‐associated pheochromocytoma is known to have a small risk of metastasis. Case presentation: The case was a 62‐year‐old Japanese male with bilateral pheochromocytoma, multiple metastases in the liver and bones, and a cardiac thrombus. Genetic testing revealed a pathological variant at codon 634 of the RET gene, thereby leading a diagnosis of MTC. We considered that the multiple metastases were due to MTC; however, a liver biopsy revealed metastasis of pheochromocytoma. Conclusion: When pheochromocytoma precedes MTC, the diagnosis of MEN2A may be difficult.